The Socio-economic Transformations in the Peri-urban of Bandung Metropolitan Area - Yanti Budiyantini; Sheilla Alviany (Journal of Infrastructure & Facility Asset Management, 2022)
Urban growth is referred to as the expansion of an urban area into the surrounding environment. The expansion gives rise to sub-urban development phenomena called peri-urbanization, which occurs in physical, economic, and social changes. This paper identifies the socio-economic transformations in the peri-urban Bandung Metropolitan Area, based on the theoretical determination of socio-economic variables and peri-urban typology. The study emphasizes the main feature of the socio-economic changes in each peri-urban typology based on the discriminant analysis. Socio-economic transformation is analyzed on the variables of population density, household economic sectors, people's education, and the number of prosperous families. A Peri-urban area is divided into three typologies: Predominantly Urban (dominantly urban characteristics), Semi-Urban, and Potential Urban Area (dominantly rural characteristics). The data and information required for the study are generated mainly from secondary sources. The study shows that socio-economic transformation occurs in each peri-urban typology at different levels of change. The different characteristics of peri-urban typology and its proximity to the city center result in a high socio-economic transformation rate.